A review on cone-beam computed tomography and its application in dentistry - Arvind Jain; Malabika Shil; C Sreepradha; Sajni Rai; Impreet Kaur; Aanchal Banka (Wolters Kluwer Medknow Publications, 2024)
Cone-beam computed tomography (CBCT), which has benefits over traditional radiography in this age of cutting-edge technology, has become increasingly popular in oral radiology. The utilization of CBCT is experiencing significant growth in several dental specialties, mainly for diagnostic purposes and treatment planning. Image acquisition and 3D imaging have helped the clinical use of cone-beam technology. The equipment has a user-friendly interface, minimum image distortion, and images compatible with many planning and simulation software applications. The present literature review aims to discuss CBCT and its various applications in dentistry.